Desempenho de soja associado à posição do fertilizante e tamanho de sementes - Sgarbossa, Maicon (2016)
The seed size used for seeding has caused doubts among soybean producers. The study aimed to determine whether there may be differences between seed size with respect to depth of fertilizer deposition. The field experiment was conducted at the Experimental Area UTFPR Campus Pato Branco, using a precision seeder for direct seeding. The design was a randomized blocks, with five repetitions. The treatments were composed by the combination of two seed sizes (large seed with 6,5 mm and 5,5 mm with small seed) and two fertilizer deposition depths in relation to the seed (fertilizer near the seed with about 3 cm away and fertilizer distant from the seeds with about 10 cm). Data were subjected to analysis of variance. When the test value F was significant at 5% probability was applied to the Duncan test for comparison of means. The shallower depth of fertilizer deposition provided larger number of pods per plant and increased number of grains per plant. Already the largest depth of fertilizer deposition provided greater plant height at 30 days after sowing and R2 stage, greater ground area mobilized, higher plant population in all periods, greater depth of deposition of seeds and a higher rate of emergency speed.